Reprogramming the immune microenvironment in lung cancer - Chen, Kai; Luo, Linqi; Li, Yong; Yang, Ge (Frontiers in Immunology, 2025)
Lung cancer remains the leading cause of cancer-related mortality worldwide, with its progression shaped not only by tumor-intrinsic factors but also by a complex and immunosuppressive tumor microenvironment (TME). Within this niche, diverse immune populations—including CD8+ cytotoxic T cells, CD4+ helper T cell subsets (Th1, Th17, Tregs), B cells, natural killer (NK) cells, tumor-associated macrophages (TAMs), and myeloid-derived suppressor cells (MDSCs)—collectively regulate immune surveillance and tumor escape. While effector lymphocytes mediate antitumor responses, their function is often attenuated by TAM- and MDSC-driven immunosuppression via cytokines (IL-10, TGF-β), metabolic disruption, and immune checkpoint expression. High densities of M2-polarized TAMs and MDSCs correlate with poor prognosis and resistance to therapy. Immune checkpoint inhibitors targeting PD-1/PD-L1 and CTLA-4 have improved outcomes in lung cancer, yet therapeutic efficacy remains limited by the immunosuppressive TME. This review outlines the functional roles of key immune cell subsets in lung cancer and highlights emerging strategies to reprogram the TME and enhance immunotherapeutic responsiveness.